Faktor- Faktor Yang Berhubungan Dengan Cakupan Persalinan di fasilitas Pelayanan Kesehatan Wilayah Kerja Puskesmas Rantau Suli Tahun 2023 - Dwi Gustin Franciska; Eltriya Septiyani (STIKes Budi Mulia Sriwijaya, 2024)
Background: Giving birth in a Health Service Facility is a recommendation from the government to reduce the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR), the legal basis is stated in Permenkes no. 97 of 2014 article 14 paragraph (1) which states